Relationship between pre-delivery stride and fast bowling performance in cricket - Bull, H. G.; Alway, P.; King, M. A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to investigate fast bowler biomechanics during the pre-delivery stride and how they associate with variables previously linked with faster ball release speeds. Kinematic bowling data was collected from 29 elite fast bowlers using 3D motion capture. Pre-delivery stride technique showed multiple significant associations with performance-related variables: more vertical take-off angles correlated with slower run-up velocity; and a larger downward landing velocity associated with less thoracolumbar flexion during the bowling action. Shallower pre-delivery stride take-off angles might therefore be recommended but physical capacity of the bowler should be considered due to the undesirable association between faster run-up velocity and greater front knee flexion at front foot contact.